3 * (х - 2) = - 10х
3х - 6 = - 10х
3х + 10х = 6
13х = 6
х =
- (2х - 5) = - 5х
- 2х + 5 = - 5х
- 2х + 5х = - 5
3х = - 5
- 3 * (х - 3) = 7
- 3х + 9 = 7
- 3х = 7 - 9
- 3х = - 2
5 * (х + 2) = 11 * (х - 3)
5х + 10 = 11х - 33
5х - 11х = - 33 - 10
- 6х = - 43
3 * (х - 2) = - 10х
3х - 6 = - 10х
3х + 10х = 6
13х = 6
х =
- (2х - 5) = - 5х
- 2х + 5 = - 5х
- 2х + 5х = - 5
3х = - 5
х =
- 3 * (х - 3) = 7
- 3х + 9 = 7
- 3х = 7 - 9
- 3х = - 2
х =
5 * (х + 2) = 11 * (х - 3)
5х + 10 = 11х - 33
5х - 11х = - 33 - 10
- 6х = - 43
х =